Heat Exchanger Design Handbook : Thermal And Hydraulic Design of Heat Exchangers 3 - BELL, Kenneth (Hemisphare, 1983)
Heat Exchanger Design Handbook : Thermal And Hydraulic Design of Heat Exchangers 3